2021
DOI: 10.1002/ppul.25263
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of proper inhaler technique and asthma control in pediatric patients with asthma

Abstract: Background Improper use of asthma inhalers is one of the potential factors of poor asthma control among children. This study aimed to assess the proper handling of asthma inhalers and asthma control in addition to factors influencing them among pediatric patients who self‐administer their inhalers. Methods A cross‐sectional study was conducted in Jordan from February 2019 to February 2020. All eligible pediatric patients with asthma attending outpatient settings were approached. The inhalation technique was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…In the present study, the most frequently made mistakes during inhaler treatment were consistent with the mistakes identified in previous studies involving patients with asthma and their caregivers (8,9,20,21). The strengths of the present study include a very high number of health professionals evaluated in a single center and the use of pre-test and post-test evaluations before and after face-toface inhaler technique training.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the most frequently made mistakes during inhaler treatment were consistent with the mistakes identified in previous studies involving patients with asthma and their caregivers (8,9,20,21). The strengths of the present study include a very high number of health professionals evaluated in a single center and the use of pre-test and post-test evaluations before and after face-toface inhaler technique training.…”
Section: Discussionsupporting
confidence: 86%
“…A checklist was prepared to assess the use of MDI and DPI (turbuhaler and diskus) devices, which are often used in the treatment of childhood asthma. It comprised the mandatory steps mentioned in the literature and was modified in accordance with our clinical experience (9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma from medication use: an under recognised burden of care Almomani et al [25] looked at stigma in children with asthma and concluded that children who were less stigmatised had a better asthma control. The tool used to look at stigma was modified to ask questions about the embarrassment that asthma patients tend to feel about 1) telling people that they have asthma; and 2) using the inhalers in front of friends or relatives.…”
Section: Impact Of Medication-related Stigma On Health Outcomesmentioning
confidence: 99%
“…Daily controller therapy with inhaled corticosteroids (ICS) can reduce chronic airway inflammation, control asthma symptoms and prevent acute exacerbations (2), yet prevalence of uncontrolled asthma remains above 50% in this age group (1). Growing evidence implicates suboptimal adherence to controller inhalers, even when children have symptoms (3)(4)(5), and improper inhaler technique among a majority of children, including lack of awareness of errors among children and their adult caregivers (6)(7)(8)(9)(10). Although global and national asthma guidelines recommend regular assessment of adherence and inhaler technique plus optimization before any step up in therapy (2,11), traditional approaches are insufficient.…”
Section: Introductionmentioning
confidence: 99%